A comparative study of surface integrity of Ti-6Al-4V alloy machined by EDM and AECG - Hascalik, Ahmet; Caydas, Ulas (Elsevier Science Sa, 2007)
The electrical discharge machining (EDM) process produces the recast layer with or without cracks on the surface that requires a remedial post-treatment in the manufacture of critical or highly stressed surfaces. One of the frequently used post-treatment processes is also the abrasive electrochemical grinding (AECG) and it has been widely used in the precision machining of difficult-to-cut materials due to an enhanced surface integrity and productivity. The aim of this study is to investigate improvability of surface integrity in terms of machining voltage, electrolyte flow rate and table feed rate parameters of AECG in EDMed Ti6Al4V alloy. Scanning electron microscopy (SEM), X-ray diffraction (XRD), energy dispersive spectrograph (EDS) and surface roughness measurement were performed to study the surface characteristics of the machined samples. Experimental results indicate that the AECG process effectively improves the surface roughness and eliminates the EDM damages completely by setting suitable grinding parameters. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: AECG; EDMed surfaces; Ti6Al4V